Small-Scale Fisheries and Aquaculture Ontology (SSFO): Labeling fish science data - Arnaud, Elizabeth; Laporte, Marie-Angélique; Delamare-Deboutteville, Jerome; Tilley, Alexander (2022)
Heterogeneous and multidisciplinary data are generated by research on sustainable global agriculture and agri-food systems. This data is analysed and often integrated into predictive models for climate change or decision-making tools for fisheries management and aquaculture production. WorldFish (CGIAR) research aims to improve the sustainability, productivity and resilience of aquatic food systems. Harmonising the labelling of aquatic foods data with controlled vocabularies will enable easier data aggregation, interpretation, and analysis. The Fisheries and Aquaculture Ontology Working Group was formed in 2019 to compile, update and contribute fishery related terms to existing controlled vocabularies. The objective is to improve the WorldFish data interoperability into the various projects, databases and repositories by (a) addressing inconsistent use of fisheries and aquaculture related terms across the datasets, (b) highlighting the missing terms in the main semantic resources, and (c) connecting and collaborating with the CGIAR Community of Practice for Ontology. An ontology is a standardised representation of the definitions and relationships of data from a specific discipline. Ontologies provide a common language for different kinds of data to be easily interpretable and interoperable allowing easier aggregation and analysis.